Utilization of Combinations of Organic Matter in Chrysanthemum Plant Cultivation - Arjana, I Gusti Made; Sudewa, Ketut Agung; Andriani, A.A. Putri Risa (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Chrysanthemums are a vital commodity in Indonesia’s floriculture industry. Their cultivation, primarily managed by small-scale farmers with limited resources, often results in suboptimal quality. Increasing chrysanthemum production and quality requires adopting appropriate, locally sourced organic materials as soil amendments. This study evaluates the impact of different organic material combinations and their dosages on chrysanthemum growth and yield. A field experiment was conducted in a greenhouse using a Nested Experiment with a Randomized Factorial Design. The results indicate that combinations of organic materials significantly influence flower stalk length, weight, and fresh flower weight. The highest economic fresh flower weight (132.13 g) was achieved using a combination of chrysanthemum residue, hydroponic media, and leaf litter at a dose of 1.5 tons per hectare, showing a 10.87% yield increase over the lowest treatment. These findings highlight the potential of organic matter integration to enhance chrysanthemum quality and farmer profitability. Contribution to Sustainable Development Goals (SDGs):SDG 2 – Zero HungerSDG 8 – Decent Work and Economic GrowthSDG 12 – Responsible Consumption and ProductionSDG 13 – Climate ActionSDG 15 – Life on Land